Compliance Mechanisms in the Framework Convention on Climate Change and the Kyoto Protocol - Campins Eritja, Mar; Fernández Pons, Xavier; Huici Sancho, Laura (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2004)
Multilateral environmental agreements usually provide for mechanisms to monitor and ensure compliance. This paper focuses on the analysis of two of the most singular mechanisms under the FCCC and the KP: the Multilateral Consultative Process and the new Compliance Procedure. The authors analyse how the European bubble plays a role in the application of such mechanisms. Those mechanisms search for a balance between facilitation and enforcement, which should be reflected at the institutional and procedural levels. In cases of noncompliance, specific consequences are associated to the concrete nature of the obligations foreseen in such international instruments.